Knowledge of, and attitudes towards, Voluntary HIV Counselling and Testing services amongst adolescent high school students in Addis Ababa, Ethiopia - Abraham A. Gatta; Gloria Thupayagale- Tshweneagae (AOSIS, 2012)
Voluntary HIV counselling and testing (VHCT) is one of the key strategies in the prevention of HIV in Ethiopia. However, utilisation of the VHCT services amongst adolescents has been reported as low by previous studies. The purpose of this study was to investigate adolescents' knowledge and attitudes towards VHCT services amongst adolescents attending high school in Addis Ababa, the capital city of Ethiopia. A cross-sectional school-based design using quantitative methods was employed to attain the objectives of the study. Data collection was done using self-administered structured questionnaires amongst 378 adolescent high school students. Data were analysed using the Statistical Package for Social Sciences (SPSS). The findings revealed that 75.7% of students are aware of the voluntary HIV counselling and testing services; 62.2% use the services and suggested that VHCT services should be located in schools and youth clubs for better access by adolescents. Thirty-two percent of respondents rated themselves at risk of HIV infection and 35.2% were not willing to disclose their HIVpositive status to anybody. The findings of the study clearly indicate a need for a more accessible voluntary HIV counselling and testing services for adolescents.